2018
DOI: 10.21037/jss.2018.09.04
|View full text |Cite
|
Sign up to set email alerts
|

Trends in cervical disc arthroplasty and revisions in the Medicare database

Abstract: Background: Due to increased postoperative complications with anterior cervical discectomy and fusion (ACDF), there has been an increasing interest in the use of cervical disc arthroplasty (CDA). Advancements in prosthetic designs and techniques have improved patient reported outcome measurements and minimized revision rates. There is a paucity in the literature regarding recent trends in CDA utilization and revision rates. The purpose of this study was to determine annual primary and revision CDA trends with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 22 publications
(21 reference statements)
1
16
0
Order By: Relevance
“…42 In the United States, CDA has experienced a high rate of annual growth in its use both as a primary therapy (20.54%) and revision therapies (5.84%), attributed to better PROs compared with ACDF. 43 CDA as a good alternative to ACDF is further supported by the results of this current study. To our knowledge, this is the largest reported cohort to date of 3-and 4-level CDA patients reporting longterm clinical outcomes.…”
Section: Discussionsupporting
confidence: 83%
“…42 In the United States, CDA has experienced a high rate of annual growth in its use both as a primary therapy (20.54%) and revision therapies (5.84%), attributed to better PROs compared with ACDF. 43 CDA as a good alternative to ACDF is further supported by the results of this current study. To our knowledge, this is the largest reported cohort to date of 3-and 4-level CDA patients reporting longterm clinical outcomes.…”
Section: Discussionsupporting
confidence: 83%
“…The commercially available database has been used extensively for orthopedic-related research. [12][13][14] The database contains over 100 million patients from the Humana insurance and Medicare insurance claims database and provides information such as diagnoses, procedures, complications, discharge dispositions, in addition to other metrics. Since the database contains deidentified information, our study was exempt from the institution's Institutional Review Board approvals.…”
Section: Materials and Methods Databasementioning
confidence: 99%
“…[68][69][70] Nevertheless, recent studies have demonstrated an increased rate of CDA use for similar pathologies. [71][72][73][74][75][76] In a retrospective review of a nationwide inpatient sample, Nesterenko et al observed an estimated 700% increase in CDA cases performed from 2005 to 2008 (344 to 2434). 76 increase was after 2013, likely secondary to more devices being approved after this date.…”
Section: Overall Trends and Costs Of Acdf And Cdamentioning
confidence: 99%